2017
DOI: 10.1038/s41598-017-00527-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics reveals biotic and abiotic elicitor effects on the soft coral Sarcophyton ehrenbergi terpenoid content

Abstract: The effects of six biotic and abiotic elicitors, i.e. MeJA (methyl jasmonate), SA (salicylic acid), ZnCl2, glutathione and β-glucan BG (fungal elicitor), and wounding, on the secondary metabolite accumulation in the soft coral Sarcophyton ehrenbergi were assessed. Upon elicitation, metabolites were extracted and analysed by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Except for MeJA, no differences in photosynthetic efficiency were observed after treatments, suggesting the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 68 publications
0
12
0
1
Order By: Relevance
“…20 While Red Sea marine invertebrates have been historically under-reported within the scientic literature, intensive investigation of Red Sea marine life has occurred over the past ten years. 8,[21][22][23] To continue efforts to identify new marine metabolites from Red Sea so coral, [6][7][8][22][23][24] herein we report three cembrene diterpenoids isolated from S. ehrenbergi (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…20 While Red Sea marine invertebrates have been historically under-reported within the scientic literature, intensive investigation of Red Sea marine life has occurred over the past ten years. 8,[21][22][23] To continue efforts to identify new marine metabolites from Red Sea so coral, [6][7][8][22][23][24] herein we report three cembrene diterpenoids isolated from S. ehrenbergi (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Here the absence of response to MeJA treatment could be related to presumably lower zooxanthellae content of L. pauciflorum suggested by its slightly paler color. Under such circumstances, the plant specific elicitor MeJA would have less pronounced effects at low density zooxanthellae, although a previous experiment showed that the symbionts readily responded at the metabolic level in Sarcophyton ehrenbergi [ 21 ]. Incubation with MeJA in the culture seawater led to decreased photosynthetic efficiency in S. ehrenbergi, but at this experiment neither the coral host nor the separately analysed zooxanthellae increased their terpenoid levels [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under such circumstances, the plant specific elicitor MeJA would have less pronounced effects at low density zooxanthellae, although a previous experiment showed that the symbionts readily responded at the metabolic level in Sarcophyton ehrenbergi [ 21 ]. Incubation with MeJA in the culture seawater led to decreased photosynthetic efficiency in S. ehrenbergi, but at this experiment neither the coral host nor the separately analysed zooxanthellae increased their terpenoid levels [ 21 ]. Nevertheless MeJA has been shown to elicit stress response in plants [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant hormone IAA (Indole-3-acetic acid) can modulate plant growth, including plant apical dominance, root formation, adversity stress adaptation and physiological aging process, by means of inducing faster and higher expression of primary response genes (Hagen & Guilfoyle, 2002). SA (Salicylic acid) is a signal molecule of plant defense reactions to abiotic stresses (Farag et al, 2017). JA (Jasmonic acid) is one of the key signal molecules inducing resistance responses of plants.…”
Section: Introductionmentioning
confidence: 99%